Erdogan's Foreign Policy Against Kurds in Syria: A Turkish Military and Political Strategy - Setiawati, Diana; Enno Haya Gladya Naranta (Law and Justice, 2022)
The situation in the Middle East is complicated by the need for Turkey to formulate a new military and political strategy . Relations between the Kurds and Turkey since the collapse of the Ottoman caliphate have been strained by the Kurds' desire for autonomous power. Until now, Kurds are still struggling to gain this legitimacy and are transforming into radical and separatist groups. Turkey under Erdogan's leadership underwent political reform from secular to democratic Islam. This includes changing Turkey's strategy to deal with Kurdish militias in Syria because Kurdish militias in Syria are considered dangerous by forming the PKK. The PKK occupies Syria's border with Turkey, so Erdogan devised a special military and political- strategic framework to stem the power of Kurdish militias. Since Turkey was ruled by Recep Tayyip Erdogan, Turkey's foreign policy has used the concept of "strategic depth" which is essential "zero problems with neighbors".  Turkey in the Erdogan era tries to represent a modern and Muslim country that encourages democracy and social justice. This affected the perspective and strategy of Turkey being used to paralyze the Kurds. In the political strategy, Turkey conducts relations with various state and non-state actors to be able to exert influence at the international level. This research aims to know how Erdogan’s foreign policy against Kurd in Syria. This research method is using normative legal research with data analyzing using case approach. This research will explain on; a) The conflict between Turkey and Kurds, b) Characteristics of Erdogan's Government, c) Turkey's Involvement in the Syrian Conflict. This research finding will be the discussion analysis on Turkey's Military and Political Strategy against Kurds in Syria and Implications of Military and Political Strategy.